Tatlo, dalawa, isa - Brocka, Lino.; Ilagan, Jay.; Bautista, Perla; Koronel, Hilda; Cinemanila Corporation (Makati City Unico Entertainment, 2007)
Three separate story about people who seek a way out the lives they have become trapped in. The first story "Mga hugis ng pag-asa" defects the story of young drug addict, Noni (Jay Ilagan), as he struggles through a drug rehabilitation program and also tries to come to terms with issues regarding his parentage. The second story tells the story of Gina (Hilda Koronel), a GI baby who arranges a meeting with her American father in the hopes that her father will take her away from the squalor of the slums where she lives. The final story concerns the frustrations of Rosenda (Lolita Rodriguez), a good daughter who has given up her own life and dreams to tend to her domineering and ailing mother.
Mga hugis ng pag-asa -- Hellow soldier -- Bukas, madilim, bukas.
A trilogy by Lino Brocka -- Container.
Directed by Lino Brocka ; producer,Cinemanila Corporation.
Jay Ilagan, Perla Bautista, Hilda Koronel...[et al].
DVD.
In Tagalog with subtitles in English.
Keywords: Detective and mystery films -- Philippines; Feature films -- Philippines